Napoleon and the World War of 1813 : Lessons in Coalition Warfighting. - Riley, J. P. (Taylor and Francis, 2013)
This analysis of the world war between Napoleon and the 6th coalition in 1813 covers operations in Europe, Spain and North America. It examines the differences between alliances and coalitions, comparing the long-term international relationships in alliances and the short-term union of coalitions.